The Bi-Directional Relationship between Periodontal Disease and Hyperlipidemia - Fentoglu, Ozlem; Bozkurt, F. Yesim (European Journal of Dentistry, 2008)
It has been proposed for several decades that infections may be responsible for the accelerated development of atherosclerosis. The initiation of the atherosclerotic plaque is ascribed to focal accumulation of lipids. This explains the importance of plasma lipids in the development of atherosclerosis. Recent reports point towards a possible association between periodontal disease and increased risk for cardiovascular disease. Thus, periodontitis and cardiovascular disease may share common risk factors, and association between periodontitis and coronary heart disease may be due to the elevated levels of plasma lipids. Epidemiological and clinical studies have also suggested that there is a relationship between periodontal disease and impaired lipid metabolism. In this review, we summarized the potential link mechanisms in the association between periodontal infection and serum lipids. (Eur J Dent 2008;2:142-149)
Keywords: Periodontal disease; Hyperlipidemia; Lipid metabolism